Rapid DNA Synthesis During Early Drosophila Embryogenesis Is Sensitive to Maternal Humpty Dumpty Protein Function. Issue 3 (22nd September 2017) - Lesly, Shera; Bandura, Jennifer L; Calvi, Brian R
Abstract: Lesly, Bandura, and Calvi show that rapid DNA synthesis during early Drosophila embryogenesis is highly sensitive to mild mutations... Problems with DNA replication cause cancer and developmental malformations. It is not fully understood how DNA replication is coordinated with development and perturbed in disease. We had previously identified the Drosophila gene humpty dumpty ( hd ), and showed that null alleles cause incomplete DNA replication, tissue undergrowth, and lethality. Animals homozygous for the missense allele, hd 272-9, were viable, but adult females had impaired amplification of eggshell protein genes in the ovary, resulting in the maternal effects of thin eggshells and embryonic lethality. Here, we show that expression of an hd transgene in somatic cells of the ovary rescues amplification and eggshell synthesis but not embryo viability. The germline of these mothers remain mutant for the hd 272-9 allele, resulting in reduced maternal Hd protein and embryonic arrest during mitosis of the first few S/M nuclear cleavage cycles with chromosome instability and chromosome bridges. Epistasis analysis of hd with the rereplication mutation plutonium indicates that the chromosome bridges of hd embryos are the result of a failed attempt to segregate incompletely replicated sister chromatids. This study reveals that maternally encoded Humpty dumpty protein is essential for DNA replication and genome integrity during the little-understood embryonic S/M cycles. Moreover, the two hd 272-9 maternal-effect phenotypes suggest that ovarian gene amplification and embryonic cleavage are two time periods in development that are particularly sensitive to mild deficits in DNA replication function. This last observation has broader relevance for interpreting why mild mutations in the human ortholog of humpty dumpty and other DNA replication genes cause tissue-specific malformations of microcephalic dwarfisms.